2003
DOI: 10.1590/s0004-282x2003000400020
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento cirúrgico da escoliose na amiotrofia espinhal progressiva

Abstract: RESUMO -Objetivo: Descrever os resultados imediatos e tardios da cirurgia para correção de escoliose em pacientes com amiotrofia espinhal progressiva (AEP). Método: 14 pacientes com AEP submetidos a cirurgia para escoliose foram selecionados para análise retrospectiva dos prontuários e radiografias, assim como para exame radiográfico e aplicação de um questionário na consulta final. O tempo médio de seguimento foi de 22 meses. A escoliose média pré-operatória foi de 78,4° pelo método de Cobb. Todos os paciente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, we cannot infer anything from this finding, since there are no studies that stratify outcomes by underlying diagnosis. 13,18 Immobility, although with a small overall percentage (2%) in this study, was reported as a complication because it is a factor that can impact hospital outcomes. 19,20 The 1 st postoperative was the day of least adherence to the proposed mobility goals (24%) and this should be a point of attention to be managed in the institutions, in conjunction with patient education and the active participation of the patient and family in postoperative planning, including information about daily goals.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, we cannot infer anything from this finding, since there are no studies that stratify outcomes by underlying diagnosis. 13,18 Immobility, although with a small overall percentage (2%) in this study, was reported as a complication because it is a factor that can impact hospital outcomes. 19,20 The 1 st postoperative was the day of least adherence to the proposed mobility goals (24%) and this should be a point of attention to be managed in the institutions, in conjunction with patient education and the active participation of the patient and family in postoperative planning, including information about daily goals.…”
Section: Discussionmentioning
confidence: 72%
“…In this study, the Cobb angle, which is an important factor when analyzing outcomes related to surgical time, for example, was not documented. 13,18 Most studies only report complications related to the intraoperative period or the most serious postoperative ones, such as infection of the surgical site and respiratory infection. In this sense, the complication rate percentages found in the literature are lower than the values observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Early spinal surgery tends to have better results because of milder scoliosis at the time of surgery and higher flexibility of the spine, such that better correction can be achieved 29,35. Furthermore, it improves sitting comfort as well as quality of life, including the patients’ self-confidence due to enhanced appearance 37,38. The aim for spine stabilization is to restore sitting ability without arm support and to avoid impingement of the ribs on the pelvis.…”
Section: Scoliosismentioning
confidence: 99%
“…Additional advantages include immediate sitting ability postsurgery and early mobilization 36. Independent of the surgical method, complications such as delayed wound healing and respiratory and neurological complications have been described for SMA patients 30,37,38. Furthermore, the anesthetic risk due to reduced respiratory function has to be considered for the surgical and postoperative planning.…”
Section: Scoliosismentioning
confidence: 99%
“…Scoliosis is a frequent manifestation in all forms of SMA, being secondary to progressive weakness of the axial muscles 10,11 . Surgical treatment is indicated in most cases, especially when the curve is greater than 45 degrees, to control curve progression and pelvic obliquity 12,13 . The surgical approach, often with the use of bone graft, makes the conventional lumbar puncture by posterior interlaminar approach a challenge in sucesso semelhante.…”
Section: Introductionmentioning
confidence: 99%